Community participation in developing educational quality for primary school in Madiun city - PARJI, F.; PRASETYA, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The objectives of this study are: (1) To analyze the role of the community in the development of quality education in basic education; (2) Analyze the quality of basic education in the city of Madiun. Data collection techniques are carried out through observation, in-depth interviews, and documentation techniques. The results of the study are: (1) the quality of basic education in the city is in a good category; (2) basic education in the city of Madiun is still low; (3) The role of the community in developing quality education in basic education is already running. RESUMEN Los objetivos de este estudio son: (1) Analizar el papel de la comunidad en el desarrollo de una educación de calidad en la educación básica; (2) Analizar la calidad de la educación básica en la ciudad de Madiun. Las técnicas de recolección de datos se llevan a cabo mediante observación, entrevistas en profundidad y técnicas de documentación. Los resultados son: (1) la calidad de la educación básica en la ciudad está en buena categoría; (2) la educación básica en la ciudad de Madiun sigue siendo baja; (3) El papel de la comunidad en el desarrollo de una educación de calidad en la educación básica está funcionando.